2017
DOI: 10.1016/j.adengl.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Acral Hemorrhagic Darier Disease

Abstract: Darier disease is an autosomal-dominant inherited condition caused by mutation of a gene, which produces a protein involved in calcium channel regulation. The disease has a variety of manifestations and lacks consistent genotype-phenotype correlations. Acral hemorrhagic Darier disease causes macules, papules, vesicles and/or hemorrhagic blisters on the extremities. Other classic signs of the disease may be present in the same patient or relatives. Histopathology reveals dyskeratosis and suprabasal acantholysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…There was Grade B evidence for the use of the oral retinoid, acitretin in improving DD 10 - 23 . In two clinical trials evaluating the use of acitretin in 14 patients, all patients experienced improvement, with one study reporting significant improvement or complete clearance in four of five patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was Grade B evidence for the use of the oral retinoid, acitretin in improving DD 10 - 23 . In two clinical trials evaluating the use of acitretin in 14 patients, all patients experienced improvement, with one study reporting significant improvement or complete clearance in four of five patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although the use of tretinoin (also known as all-trans-retinoic acid, retinoic acid or vitamin A acid) was the most frequently reported topical treatment for DD, the evidence for its efficacy was contradictory and of limited quality (Grade C). 8 , 12 , 19 , 57 - 64 In Goh’s retrospective study of eight patients treated with topical retinoic acid, only two experienced mild benefit from this treatment. 12 In one controlled trial of one patient with DD, areas treated with topical all-trans-retinoic acid were moderately improved, meanwhile placebo-treated areas were unchanged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesions tend to become confluent and may form papillomatous masses; they generally worsen during the summer. Other cutaneous findings include cobblestone papules of the mucosa, palmoplantar pits, verrucous lesions on the dorsal hands and feet, and red and white longitudinal nail streaks with distal ‘V’ nicking . Various studies have found a high frequency of psychiatric manifestations in patients with KF, such as epilepsy, intellectual impairment and mood disorders …”
Section: Discussionmentioning
confidence: 99%
“…Dear Editors, Darier's disease (DD) is an infrequent autosomal dominant genodermatosis related to mutations in the ATP2A2 gene, which encodes the sarcoplasmic reticulum calcium ATP ase pump SERCA2. Many different forms of DD have been described [1][2][3], including clinicalpathological variants such as the hypopigmented [4], hypertrophic [5], linear or Blaschkoid [6], hemorrhagicacral [7], vesiculobullous [8] and comedonal [5,[9][10][11][12][13][14][15][16][17][18]. This variety poses a real diagno stic challenge.…”
mentioning
confidence: 99%